ANALYSIS OF TEACHERS’ READINESS IN TEACHING ENGLISH AT ELEMENTARY SCHOOL - Febrina Anggreni; Ahmad Talib; Asriati Asriati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Teachers’ readiness in elementary school teaching is becoming an issue since the government said that English will become a mandatory subject in 2027/2028. This study aims to analyse how the readiness of teachers in teaching English at elementary school, as it significantly impacts the quality of learning. This research was conducted at SDIT Al-Iman Maros. There were two homeroom teachers in grade 3 as the subject of this research. The researchers administered observations and interviews to collect the data. The results found that the cognitive readiness is represented by teachers’ understanding of basic teaching materials. It was also found that the physical readiness, the teachers derive energy from their students' enthusiasm. In terms of mental readiness, teachers show interest from effort by searching information on social media. It is because they also have motivation for their responsibility as teachers, and also want to make students familiar with basic English at the higher education.